2021
DOI: 10.1159/000521164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 1-Year Controlled Lifestyle Intervention on Body Weight and Other Risk Markers (the Healthy Lifestyle Community Programme, Cohort 2)

Abstract: Introduction: The prevalence of obesity is high and increasing worldwide. Obesity is generally associated with an increased risk of chronic disease and mortality. The objective of the study was to test the effect of a lifestyle intervention on body weight and other chronic disease risk markers. Methods: A non-randomized controlled trial was conducted, including mostly middle-aged and elderly participants recruited from the general population in rural northwest Germany (intervention: n = 114; control: n = 87).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 73 publications
4
41
0
Order By: Relevance
“…The present study had the aim of examining the effect of a community-based lifestyle intervention on changes in mean and max ccIMT (among other CVD markers (16) ). While the intervention resulted in significant dietary improvements, in line with the recommendations given, physical activity did not significantly increase over the course of 1 year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study had the aim of examining the effect of a community-based lifestyle intervention on changes in mean and max ccIMT (among other CVD markers (16) ). While the intervention resulted in significant dietary improvements, in line with the recommendations given, physical activity did not significantly increase over the course of 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intake was assessed with semi-quantitative 3-d food protocols. Adherence to dietary recommendations was assessed with the plant-based diet index (PDI), healthful PDI (hPDI) and unhealthful PDI (uPDI) (18) (as described previously (16) ). As the association of the intakes of potatoes, fish, eggs and dairy with ccIMT are less certain, whereas hPDI includes these food groups as negatives, we also conducted a post hoc analysis with a modified hPDI (excluding the food groups potatoes, fish, eggs and dairy).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies demonstrated that increased consumption of vegetable foods in older people can reduce inflammation [28 ▪▪ ,29], and improve kidney function [30], cardiometabolic and cardiovascular health [31–33]. A systematic review also highlighted that dietary patterns in older adults involving higher consumption of vegetables, fruits, legumes, nuts, whole grains, unsaturated vegetable oils, fish and lean meat or poultry were associated with a decreased risk of all-cause mortality [3].…”
Section: Plant Food Matrix and Its Health Benefits For Older Peoplementioning
confidence: 99%